Perbedaan Kemampuan Akademik Anak Usia Sekolah Dasar Di Panti Asuhan: Studi Kasus Latar Belakang Dan Stimulasi Belajar - Rindiantika Putri Andini (LPPM Universitas Proklamasi 45, 2026)
This study aims to analyze the influence of family background and learning stimulation before entering an orphanage on children's academic development, as well as to identify differences in academic abilities based on prior stimulation experiences. The study uses a qualitative approach with a case study design. Data collection was conducted through observation and unstructured interviews with foster children and orphanage staff. The results of the study indicate that children who experience limited learning stimulation from an early age tend to face obstacles in academic development, even in a more supportive environment. The findings also reveal that economic conditions are not the sole determinant of academic ability, but rather the quality of learning stimulation the child receives from an early age. The difference in stimulation before entering the nursing home becomes the dominant factor.